2019
DOI: 10.1177/1455072519847014
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress in Norwegian SUD-therapists: Symptoms and related factors

Abstract: This study examined the prevalence of secondary traumatic stress (STS) among substance-abuse therapists in relation to burnout, work-related stressors, as well as peer and leader support. Methods: A quantitative cross-sectional design examining 383 Norwegian substance-abuse therapists. Electronic surveys were distributed to practitioners in Norway via email and social media. Results: A total 22% of the respondents reported experience of secondary trauma, with the most frequently reported symptoms being flashba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…; ztime difference. By careful analysis of the items contained in the two dimensions of C-STSS, it can be found that the first dimension-stress dimension (items 1,4,5,7,8,9,11,15,16,17) mainly describes the influence of STS on helpers' daily life and psychological state (including sleep, mood, concentration, enthusiasm, etc.). And dimension 2-invasion and avoidance dimension (items 2, 3, 6, 10, 12, 13, 14) mainly describe the content related to the trauma victims they help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; ztime difference. By careful analysis of the items contained in the two dimensions of C-STSS, it can be found that the first dimension-stress dimension (items 1,4,5,7,8,9,11,15,16,17) mainly describes the influence of STS on helpers' daily life and psychological state (including sleep, mood, concentration, enthusiasm, etc.). And dimension 2-invasion and avoidance dimension (items 2, 3, 6, 10, 12, 13, 14) mainly describe the content related to the trauma victims they help.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, STSS has become the standard tool for assessing STS. It has been used by doctors, nurses, midwives, respiratory therapists, mental health workers and other social workers in many regions (9)(10)(11)(12). It has been translated into Hungarian (13), French (14), German (15), Japanese (16) and other languages.…”
Section: Introductionmentioning
confidence: 99%
“…Many work-related studies have been conducted on STS, which could inform the emergent streams of traumatic stress research in the management literature (Branson, 2019; Molnar et al , 2017). However, in the same way, ASD, PTSD and cPTSD have important differences, STS has its own pattern of symptoms and work-related consequences, including exhaustion and a propensity for job burnout (Figley, 1995; Johansen et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Personally, social workers are advised to maintain self-care to reduce the risk of STS (Quinn et al, 2019) and enhance resilience (Johansen et al, 2019). One technique that can be categorized as self-administered selfcare is Self-Induced Unclassified Therapeutic Tremors (SUTT).…”
Section: Based On the Polyvagal Theory Proposed Bymentioning
confidence: 99%